Safety Jacket for Women - Aditi More,; N. P. Zinjad,; Aaishwarya Bagul,; Akshay Jagtap,; Gayatri Nawale, (Journal of Electronic Design Engineering, 2021)
The primary issue on any girl's mind in the global scenario is obsessed about her wellbeing and the abuse problems. The sole a girl's nightmare does not know when they will be able to move openly on the sidewalks, even at odd hour’s concerned about their wellbeing. This initiative proposes a new technology for women's defense. This paper is based on Women who need protection so they don't feel powerless. The formalized paraphrase of the system is made up of different modules such as GSM and GPS, an SD card, a shock circuit, a buzzer, a monitor, and a Raspberry Pi-3 module. Today, there are several incidents involving women. It was beyond time for all women to get together. Alterations this paper focuses on women's protection. Women are feeling secure. This paper discusses protection. Women's electronic devices integrated into public vehicles such as taxis, coaches, and auto-rickshaws women are being molested, abducted, and raped today being harassed by the driver. Women have a unique influence in each region. Sports, dance, school, and industry are only a few examples in politics as well. Women are taking the lead in every sector. Are Indian girls truly safe? We still get the answer. No, as a result, the implemented electronic device is installed in the jacket with GPS, GSM, a camera, and a shock circuit buzzer and SD card interfaced with Raspberry Pi -3 boards to control all of the above.